Socio-Economic Life of the Chinese Community - Rozi; Setyawan, Ryand Daddy (AFEBI Economic and Finance Review, 2023)
The discourse related to the socio-economic life of the Chinese community in Belitung Regency is certainly interesting to study. Moreover, there are quite a lot of ethnic Chinese in Belitung Regency. Therefore, the researcher feels that this research is important to do to see more about the socio-economic life of the Chinese community there. The type of this research is field research using a descriptive analysis approach. Researchers collect data by means of interviews, observation, and documentation. The results of this study can be understood that the existence of ethnic Chinese greatly influences the socio-economic life in Belitung Regency. In social life they can mingle and interact well with indigenous peoples. In terms of economic life, their existence is able to influence the economic sector of the local community. Keywords: Socio, Economic, Chinese, Belitung Regency